Pengembangan Multimedia Interaktif Fisika Untuk Meningkatkan Pemahaman Konsep Siswa SMP - nilam cahaya; Muhammad Subhan; Eka Rahmawati (GRAVITY EDU : Jurnal Pembelajaran dan Pengajaran Fisika, 2022)
This research aims to increase understanding of concepts through interactive media This research is research and development (Research and Development) which adapts the ADDIE development model. Subjects in this study are students of SMPN 11 Langgudu in class XI IPA. While the object of research is media development interactive learning using Microsoft PowerPoint material content and animated visualization on hydrostatic pressure material. Collecting data in research using a scale questionnaire 5 with data analysis used to determine the feasibility of the media interactive learning is descriptive qualitative with percentages. Based on research results 1) Assessment of the feasibility of interactive learning media by educators averaged 3.61 in the very good category while eligibility is equal to 90.36% with a very feasible category. 2) Assessment questionnaire validation by educators obtained an average of 3.50 with a very good category while the eligibility is equal to 87.5% with a very decent category. 3) The media expert's assessment obtained an average of 4.74 with a very good category while the eligibility was 97.58%. 4) the assessment of the results of material experts obtained an average of 4.61 with a very good category with a very feasible category while the feasibility is equal to 88.26%. 5) The response of class XI IPA students with their presence of interactive learning media using Microsoft Powerpoint on hydrostatic pressure material. In the limited trial, an average score of 3.50 (very good) was obtained and feasibility of 70.50% (very feasible). Finally, this interactive learning media is expected to provide motivation to educators and students in implementation of learning in schools to be better